Health Belief Model Factors to Medication Adherence among Hypertensive Patients in Punti Kayu Public Health Center Palembang, Indonesia - Arindari, Dewi Rury; Suswitha, Dessy (University of Muhammadiyah Malang, 2020)
Introduction: Health Belief Model is one of the factors that influence medication adherence. The World Health Organization (WHO) has identified medication adherence as the primary indication of treatments effectiveness for hypertensive patients. The number of medication adherence on people with hypertension is decreasing in the world, including Indonesia. Objective: The aims of this paper was to examine the relationship between perceived susceptibility to develop the complications of hypertension, perceived severity of hypertension complications, perceived benefits of medication adherence, perceived barriers to medication adherence and medication adherence. Result: There were significant statistically relationships between perceived susceptibility to develop the complications of hypertension, perceived severity of hypertension complications, perceived benefits of medication adherence, perceived barriers to medication adherence and medication adherence. Discusion: The patients who have high perceptions about susceptibility to develop the hypertension complication, severity of the complications of hypertension, the benefit of medication adherence, reduce barriers to medication adherence more likely adhering to their medications.